Enhancing media literacy to prevent violence against women and children in PC ‘Aisyiyah Ngampilan - Adhianty Nurjanah; Nano Prawoto; Riski Apriliani (Community Empowerment, 2024)
Pimpinan Cabang Aisyiyah (PCA) Ngampilan, at the Law and Human Rights Council, emphasized studies with a gender perspective that are in accordance with Islamic values, focusing on preventing violence against women and children. Community service is conducted to enhance media literacy related to preventing violence against women and children at PCA Ngampilan. This service aims to augment knowledge and provide assistance to PCA Ngampilan and the community regarding the protection of women and children using an Islamic approach. Activities involve socialization and content creation training about the importance of protecting women and children. This activity resulted in an 85% increase in knowledge about preventing violence against women and children.